2015
DOI: 10.1186/s13099-015-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

Draft genomes of four enterotoxigenic Escherichia coli (ETEC) clinical isolates from China and Bangladesh

Abstract: BackgroundEnterotoxigenic Escherichia coli (ETEC) is an important pathogen that causes childhood and travelers’ diarrhea. Here, we present the draft genomes of four ETEC isolates recovered from stool specimens of patients with diarrhea in Beijing, China and Dhaka, Bangladesh, respectively.ResultsWe obtained the draft genomes of ETEC strains CE516 and CE549 isolated in China, and E1777 and E2265 isolated in Bangladesh with a length of 5.1 Mbp, 4.9 Mbp, 5.1 Mbp, and 5.0 Mbp, respectively. Phylogenetic analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Although the expression levels were not significantly changed in this study, the findings are confirmed by our previous work [8]. Genome analysis showed that both strains also express additional virulence genes: cexE, clyA, eatA, ecpA, and fimH [18]. These genes were not significantly changed.…”
Section: Expression Of Etec Virulence Factors Is Slightly Higher During Exponential Growthsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the expression levels were not significantly changed in this study, the findings are confirmed by our previous work [8]. Genome analysis showed that both strains also express additional virulence genes: cexE, clyA, eatA, ecpA, and fimH [18]. These genes were not significantly changed.…”
Section: Expression Of Etec Virulence Factors Is Slightly Higher During Exponential Growthsupporting
confidence: 87%
“…The ETEC strains E1777 and E2265 (LT STh/CS5+CS6), both isolated from adult patients with watery diarrhea in Dhaka Bangladesh in 2005 and 2006, respectively, were used in this study [12,48]. The whole-genome sequences of the two strains are available [18], including a complete assembled chromosome and two plasmids of 142 and 78 kbp, respectively, for E2265 [11,48]. Bacteria from frozen stock vials were grown on blood plates, and 10 colonies were picked and grown under shaking conditions in 10 ml of LB medium to OD600 = 0.8 (10 9 bacteria/ml) to be used as a starting culture.…”
Section: Strains Growth Conditions and Bacterial Enumerationmentioning
confidence: 99%
“…The clinical ETEC isolates E1777 and E2265, which both express the CS5 and CS6 colonization factors and the LT and STh enterotoxins, were used for transcriptomic and proteomic analyses (Supplementary Table S3). The strains were isolated from stool samples from adults with acute diarrheal disease at the hospital of the International Centre for Diarrheal Disease Research (icddr,b) in Dhaka, Bangladesh, in April 2005 and March 2006, respectively 17,66 . The toxin profile was determined with ELISA and PCR, and the colonization factor profile was determined with dot-blot assays for various CFs 25 .…”
Section: Methodsmentioning
confidence: 99%
“…The toxin profile was determined with ELISA and PCR, and the colonization factor profile was determined with dot-blot assays for various CFs 25 . Both strains have been sequenced and belong to the global phylogenetic lineage L5 and are multilocus sequence type 443 37,66 . Clinical isolates from the University of Gothenburg ETEC collection were used for additional studies of gene expression and cell adhesion (Supplementary Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, using ResFinder, no acquired resistance genes were found for E2265 (sample 5), while ARG-annot confirmed chromosome-bound ampicillin resistance by ampC (see Table S4 in the supplemental material). This isolate has been described previously ( 43 , 44 ). Regarding the ETEC strains found as coinfecting pathogens, E2266 (sample 9) and E2267 (sample 16) harbored four and three antibiotic resistance genes each, respectively.…”
Section: Discussionmentioning
confidence: 99%